Motives of sanctioning: Equity and emotions in a public good experiment with punishment - Paolo Crosetto; Werner Güth; Luigi Mittone; Matteo Ploner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
We study conditional cooperation based on a sequential two-person linear public good game in which a trusting first contributor can be exploited by a second contributor. After playing this game the first contributor is allowed to punish the second contributor. The consequences of sanctioning depend on the treatment: whereas punishment can reduce inequality in one treatment, it only creates another inequality in the other. To capture the effect of delay on punishment both treatments are run once with immediate and once with delayed punishment. Moreover, to investigate the effect of pure voice, all four treatments are also run in a virtual condition with no monetary consequences of punishment. Results show the emergence across all conditions of a strong norm of conditional cooperation. Punishment is generally low, it is higher when not delayed and it is not used to reduce inequality in payoffs. The main motive of sanctioning appears to be the need to punish a violation of the reciprocity norm, irrespective of monetary consequences.
Keywords: C70; C72; C92; H41; 330; Public good games; Punishment; Experiments; Conditional cooperation; Extensives Spiel; Öffentliches Gut; Strafe; Kooperation; Test